International Monetary Fund Annual Report 2008 : Making the Global Economy Work for All. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 2008)
The Annual Report 2008 to the Board of Governors reviews the IMF's activities and policies during the financial year (May 1, 2007, through April 30, 2008). There are five chapters: (1) Overview: Refocusing the IMF; (2) Developments in the Global Economy and Financial Markets; (3) Fostering Macroeconomic and Financial Stability and Growth Through Surveillance; (4) Program Support and Capacity Building; and (5) Governance, Organization, and Finances. The full financial statements for the year, other appendixes, and materials supplementing the text are provided on a CD-ROM.